Plankton and dissolved nutrient data from 2016 mesocosm experiment manipulating Si:N and copepod grazing on Baltic Sea plankton community - Makareviciute-Fichtner, Kriste; Matthiessen, Birte; Lotze, Heike K; Sommer, Ulrich (PANGAEA, 2020)
Phytoplankton, microzooplankton, copepod and dissolved nutrient data from a mesocosm experiment, which took place in summer 2016. A range of Si:N ratios and two levels of copepod grazing pressure were manipulated on a natural plankton community in Kiel Bay, Southern Baltic Sea, Germany.
Keywords: mesocosm; nutrient ratios; Phytoplankton; silicon; stoichiometry; Zooplankton